What happens after the implementation of electronic locking devices for adolescents at cigarette vending machines?: a natural longitudinal experiment from 2005 to 2009 in Germany - Schneider, Sven; Gruber, Johannes; Yamamoto, Shelby; Weidmann, Christian (Nicotine & tobacco research, 2011)
As of January 01, 2007, electronic locking devices based on proof of age (electronic cash cards or European driving licenses) were installed on 500,000 cigarette vending machines across Germany to restrict the purchase of cigarettes to those over the age of 16 years. In 2009, the age limit was raised to 18 years. The aim of this study was to compare the number of cigarette vending machines and other commercial sources before and after the enactment of the new law and to examine the association between commercial cigarette sources and area socioeconomic status (SES).We recorded and mapped using Geographical Information System software the total number of commercial cigarette sources in 4 selected districts in the major German city of Cologne. The city was the ideal setting for this study as we were able to use existing sociogeographical data from this area. We compiled a complete inventory of commercial cigarette sources in autumn 2005 and 2009. An interim inventory was also completed in 2007.Between 2005 and 2009, the total number of cigarette sources decreased from 369 to 325 within the study area. Although the most obvious reduction was detected in the number of outdoor vending machines (−44%), the number of indoor vending machines also decreased by 5%. In 2005 as well as in 2009, we found significantly fewer commercial cigarette sources in districts with above-average SES than in districts with below-average SES.Although the number of overall cigarette vending machines decreased, the disparity in distribution of cigarette sources between socially advantaged and disadvantaged areas increased.
Gesehen am 24.10.2022
Published: 18 April 2011